2022
DOI: 10.1002/phar.2722
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin area under the curve versus trough only guided dosing and the risk of acute kidney injury: Systematic review and meta‐analysis

Abstract: Vancomycin is commonly used to treat methicillin-resistant Staphylococcus aureus infections and is known to cause nephrotoxicity. Previous Vancomycin Consensus Guidelines recommended targeting trough concentrations but the 2020 Guidelines suggest monitoring vancomycin area under the curve (AUC) given the reduced risk of acute kidney injury (AKI) at similar levels of efficacy. This meta-analysis compares vancomycin-induced AKI incidence using AUC-guided dosing strategies versus troughbased monitoring. Literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…AUC is a widely used evaluation index. AUC is an index to measure the performance of binary classification model, which measures the probability that positive samples are ranked before negative samples in the test set, reflecting the ranking ability of the model [38,39]. is paper uses AUC as an evaluation index to measure the performance of employment recommendation, and its calculation method is as follows:…”
Section: Discussion and Analysis Of Resultsmentioning
confidence: 99%
“…AUC is a widely used evaluation index. AUC is an index to measure the performance of binary classification model, which measures the probability that positive samples are ranked before negative samples in the test set, reflecting the ranking ability of the model [38,39]. is paper uses AUC as an evaluation index to measure the performance of employment recommendation, and its calculation method is as follows:…”
Section: Discussion and Analysis Of Resultsmentioning
confidence: 99%
“…Nephrotoxicity is the most significant adverse effect. Some risk factors for vancomycin-association nephrotoxicity should be warned, such as the combination of piperacillintazobactam (PTZ), everity of illness, pre-existing kidney disease, and so on (Fiorito, Luther, Dennehy, LaPlante, & Matson, 2018;Abdelmessih et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Some observational studies and meta-analyses have suggested that AUC-guided vancomycin dosing, which may lead to lower nephrotoxicity than trough-guided dosing. [7][8][9][10] The therapeutic AUC range should be complied with on the second day. 9,11 Bayesian forecasting using a population pharmacokinetic (PopPK) model and measured concentrations is an increasingly popular approach for estimating AUC, and is a key component of model-informed precision dosing (MIP-D).…”
Section: Introductionmentioning
confidence: 99%
“…The updated therapeutic drug monitoring (TDM) guidelines for vancomycin recommend a narrow therapeutic AUC range of 400–600 μg・h/mL, based on the achievement of an AUC/MIC ratio of 400 for clinical efficacy and AUC of 600 μg・h/mL for lower nephrotoxicity 4–6 . Some observational studies and meta‐analyses have suggested that AUC‐guided vancomycin dosing, which may lead to lower nephrotoxicity than trough‐guided dosing 7–10 . The therapeutic AUC range should be complied with on the second day 9,11 …”
Section: Introductionmentioning
confidence: 99%